Moderasi Beragama Menurut Muhammadiyah - Ramadhani, Novrima; Muh.Nur Rochim Maksum (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
This research aims to analyze the concept of religious moderation in Muhammadiyah's view and its role in developing the concept. Using a literature study-based qualitative method, data were obtained from primary and secondary sources such as books, documents, and scientific journals. Data validity was tested through triangulation of techniques, sources, and time. The results showed that Muhammadiyah views religious moderation as a middle stance between two extremes, fair and balanced. This is reflected in the attitude of washatiyyah, tolerant, open, and peace-loving. Muhammadiyah defines the concept of moderation in three dimensions: 1) wasatha as something very good, equivalent to khair, likened to an oasis in the desert by Imam Al-Qurthubi; 2) wasatha as a non-extreme attitude in worship and muamalah; 3) wasath as behavior according to science and law, embodying a just attitude that puts everything in its proportion.